Optimization of Solar Energy Based Decorative Lights for Sustainable Tourism Development: Optimalisasi Lampu Hias Berbasis Energi Surya untuk Pengembangan Pariwisata Berkelanjutan - Nila Alia; Widjanarko; Fengky Adie Perdana; Lisa Agustriyana; Etik Puspitasari; Pondi udianto; Yoyok Heru Prasetyo Isnomo (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
Sumberingin Bath is one of the natural tourist destinations located in Wringinsongo Village, Tumpang District, Malang Regency, East Java. This bathing site features a clear and refreshing spring, attracting many visitors from various regions. However, Sumberingin Bath has tourism potential that has not been fully optimized, particularly in the area of night tourism. The objective of this community service project is to develop a decorative lighting area powered by renewable energy at Sumberingin Bath. The methodology employed includes the development of decorative lighting infrastructure, providing training to the community on the management, maintenance, and installation of lights integrated with a solar power system, and creating a selfie tourism program that leverages the beauty of decorative lights to enhance the destination's appeal on social media. The results of this community service initiative offer solutions to the issue of limited lighting and the need to extend the operational hours of the tourist site, while also increasing knowledge and adding value to the location as a renewable energy-based night tourism destination. A total of more than 40 decorative lights were installed, with an average power consumption of 1,200 watts. The energy for these lights is derived from renewable energy stored in a powerwall system with a capacity of 14,400 watts